2020
DOI: 10.1038/s41598-019-57387-7
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence mediated red spherulocyte sorting provides insights into the source of spinochromes in sea urchins

Abstract: Red spherule cells (RSCs) are considered one of the prime immune cells of sea urchins, but their detailed biological role during immune responses is not well elucidated. Lack of pure populations accounts for one of the major challenges of studying these cells. In this study, we have demonstrated that live RSCs exhibit strong, multi-colour autofluorescence distinct from other coelomocytes, and with the help of fluorescence-activated cell sorting (FACS), a pure population of live RSCs was successfully separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
(81 reference statements)
1
23
2
Order By: Relevance
“…Spinochromes easily fragment via the removal of H 2 O, CO, and CO 2 [ 48 , 49 ]. In the experimental sections in previous reports by Brasseur et al [ 12 , 45 , 46 , 47 ], it was indicated the mass spectrometric equipment used allows the obtaining of high-resolution mass spectra and of MS/MS fragmentation of quinonoid pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Spinochromes easily fragment via the removal of H 2 O, CO, and CO 2 [ 48 , 49 ]. In the experimental sections in previous reports by Brasseur et al [ 12 , 45 , 46 , 47 ], it was indicated the mass spectrometric equipment used allows the obtaining of high-resolution mass spectra and of MS/MS fragmentation of quinonoid pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Coelomocytes, however, expressed fmos from clade 1, but not the other fmos ( Figure 5E ). These cells are diverse in morphology and putative function, of which the red spherule cells are known to produce echinochrome and spinochrome ( Coates et al, 2018 ; Hira et al, 2020 ). In the pigment biosynthesis pathway, the enzyme pks1 is upstream of the fmos in the biosynthetic pathway of echinochrome.…”
Section: Resultsmentioning
confidence: 99%
“…We used the available data of S. purpuratus quantitative RNA expression through development (http://www.spbase.org:3838/quantdev/) as an additional tool to determine the temporal expression of representative genes from the 4 clades of fmos. (Coates et al, 2018;Hira et al, 2020). In the pigment biosynthesis pathway, the enzyme pks1 is upstream of the fmos in the biosynthetic pathway of echinochrome.…”
Section: Expression Of Unique Pigment Genes Identified By Scrna-seqmentioning
confidence: 99%
See 2 more Smart Citations